The Role of knowledge Management Processes in the Tax Performance: AnApplied Research in the General Tax Authority (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The research aims to measure the relationship and impact of the operations of the knowledge of management of the six dimensions (diagnosis knowledge, define knowledge objectives, knowledge generation, knowledge storage, distribution of knowledge, application of knowledge) in the fiscal performance of the General Authority for taxes of the four dimensions (financial, customers (taxpayers), Operations Interior, learn and grow), the research aims also to the use of computerized programs for training and career development of the Authority that helps to add knowledge workers in the Authority, and to reach an appropriate arrangement for knowledge management processes in the Authority, as well as analysis of the reality of the Authority to get to know the level of overall performance it has use researcherto measure the questionnaire prepared on the basis of previous studies and additions added by the jury and researcher variables, was chosen as a random sample to represent the research community,where he distributed the questionnaire on the (234) people occupy different positions in the General Authority for taxes, it was to use a lot of statistical methods to measure the research variables (such as arithmetic mean, standard deviation,simple regression ... etc), and in the light of the findings andanalyzes research found a set of results was the most important, the presence of the effect of the dimensions of knowledge management processes in the tax performance dimensions, and theresearcher presented a set of recommendations, notably the interest the application of knowledge management processes, which in turn achieved a sound performance to tax in the General Authority for taxes.